Incidence and Factors of Carbapenems Resistant Enterobacteriaceae in Pediatric patients Songklanagarind Hospital - Viriyasuk, Chuanpit; Hathaipitak, Wanrudee; Kaewvichit, Namtip (Princess of Naradhiwas University Journal, 2023)
This descriptive retrospective research aims 1) to study the incidence of bacterial infection in Carbapenems Resistant Enterobacteriaceae, factors related to bacterial infection with Carbapenems Resistant Enterobacteriaceae and the impact of group bacterial infection Carbapenems Resistant Enterobacteriaceae in pediatric patients admitted to Songklanagarind Hospital. The sample group was 116 pediatric patients with Carbapenem Resistant Enterobacteriaceae (CRE) admitted to Songklanagarind Hospital, detected between January 1, 2017 and December 31, 2019. The instrument consisted of two record forms: 1) a personal data record form and data on factors related to the treatment of drug-resistant infections and 2) a record form for recording the effects of drug-resistant infections. The instrument was validated and received CVI=1. Data were analyzed by descriptive statistics and Chi-square test. The results showed that 1) The incidence of bacterial infection in the group Enterobacteriaceae was found that 81.03% of drug-resistant infection came from outside Songklanagarind Hospital 2) Related factors to Carbapenems Resistant Enterobacteriaceae in pediatric patients admitted to Songklanagarind Hospital were to receive antibiotics. There was a statistically significant difference at the 0.05 level and 3) The effect of bacterial infection Carbapenems Resistant Enterobacteriaceae in pediatric patients admitted to Songklanagarind Hospital was the length of hospital stay. There was a statistically significant difference at the 0.05 level.